PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 5 KOTA JAMBI - Harman Harman (Jurnal Ilmiah Dikdaya, 2018)
The low learning outcomes of mathematics students of SMP Negeri 5 Kota Jambi become the background of this research. One of the causes is less optimal learning process in school. The role of teachers who are more active in the learning process causes students to only receive the material and record it so as to cause a sense of boredom and tend to be passive. Cooperative learning model Talking Stick type is expected to help teachers in the delivery of teaching materials well, so as to improve student learning outcomes. This study is an experimental research that aims to see the results of learning mathematics through cooperative learning model type of talking stick with conventional learning. The population in this study is all students of class VIII SMP Negeri 5 Kota Jambi. The sample class is class VIII A as experiment class and class VIII C as control class. Based on the results of research conducted on the final test score (post-test), obtained the average value of the experimental class of 76.5 and the results of the average grade of control class 70.9, and from the results of hypothesis test obtained t count of 2.13 and ttable of 1.68. From the calculation shows that t count is bigger than ttable so H0 is rejected and H1 accepted. So it can be concluded that the results of learning mathematics students using cooperative learning model type of talking stick higher than the mathematics learning outcomes of students through conventional learning.Keywords: Learning Outcomes, Cooperative Learning Model Type Talking Stick, Conventional Learning